Financial Sanctions, Oil Revenues and Monetary and Fiscal policies in Iran: DSGE Model - Samira Heydarian; Mosayeb Pahlavani; Seyed Hossein Mirjalili (International Journal of Business and Development Studies, 2024)
Financial sanctions have many economic consequences for oil-exporting economies. The sanctioned economy adopts economic policies to deal with it. This paper examines the relationship between financial sanctions, oil revenues, and monetary and fiscal policies in Iran and explicates how financial sanctions have affected Iran's access to oil revenues. It also examines the role of fiscal and monetary policies in financial stability and resilience in Iran's economy. To this end, we employed a DSGE model with the new Keynesian approach. The results indicate that the interest rate, consumption, imports, and inflation have a positive reaction to the oil revenue shock resulting from financial sanctions. However, the production, export, private sector investment, and oil sales indicate a negative reaction to the oil revenues' shock. Regarding the monetary policy shock, the reaction of production and consumption to the shock is positive. However, the reaction of oil sales and interest rates to this shock is negative. In terms of financial policy shock, production, consumption, investment, and export indicated a positive reaction to this shock. However, the interest rate, imports, and oil sales indicated a negative reaction to the fiscal policy shock. Monetary and fiscal policy shocks increase the effect of financial sanctions for a short period, while monetary policy shocks reduce the effect of financial sanctions for three periods. Therefore, monetary policy has been more effective than fiscal policy in reducing the effect of financial sanctions.
Keywords: 330; Financial sanction; Monetary policy; Fiscal policy; Oil revenue